2017
DOI: 10.1111/cas.13387
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effect of cisplatin given with a lymphatic drug delivery system on false‐negative metastatic lymph nodes

Abstract: Systemic administration of drugs into the blood circulation is standard treatment for prevention of metastasis. However, systemic delivery cannot maintain sufficiently high concentrations of anticancer drugs in lymph nodes (LN). Here, we show that giving cisplatin (CDDP) using a lymphatic drug delivery system (LDDS) has the potential to treat false‐negative metastatic LN. We found that in MXH10/Mo‐lpr/lpr mice, which develop systemic swelling of LN up to 10 mm in diameter, accumulation of indocyanine green (IC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 25 publications
1
36
0
Order By: Relevance
“…False‐negative metastatic LNs are those that contain tumor cells but, due to the early stage of tumor development, have a size and shape similar to those of LNs not hosting tumor cells. The LDDS is a new approach to treat or prevent LN micrometastasis, and we have previously demonstrated this novel therapeutic concept . The LDDS operates by injecting drugs into sentinel (upstream) LNs in order to deliver them to downstream metastatic LNs in the lymphatic network and maintain high concentrations of drug within the targeted LNs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…False‐negative metastatic LNs are those that contain tumor cells but, due to the early stage of tumor development, have a size and shape similar to those of LNs not hosting tumor cells. The LDDS is a new approach to treat or prevent LN micrometastasis, and we have previously demonstrated this novel therapeutic concept . The LDDS operates by injecting drugs into sentinel (upstream) LNs in order to deliver them to downstream metastatic LNs in the lymphatic network and maintain high concentrations of drug within the targeted LNs.…”
Section: Introductionmentioning
confidence: 99%
“…The LDDS is a new approach to treat or prevent LN micrometastasis, and we have previously demonstrated this novel therapeutic concept. 23 The LDDS operates by injecting drugs into sentinel (upstream) LNs in order to deliver them to downstream metastatic LNs in the lymphatic network and maintain high concentrations of drug within the targeted LNs.…”
mentioning
confidence: 99%
“…Development of a minimally invasive treatment to prevent lymph nodemediated hematogenous metastasis is desirable, and we have previously reported (using the same animal model) that anticancer drugs can be injected into an upstream lymph node to treat micrometastasis in a downstream lymph node. [31][32][33] A lymphatic anticancer drug delivery system can remove the origin of lymph node-mediated hematogenous metastasis by targeting micrometastases in lymph nodes, avoiding surgical intervention and preventing the risk of activation of distant metastatic lesions by lymph node resection. Therefore, this novel cancer chemotherapy approach may be a promising technique that should be further investigated in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, false-N0 metastatic LNs can be a source of hematogenous metastasis. The importance of false-N0 LNs in distant metastasis is supported by the results of clinical trials suggesting that LN dissection [25,26] and sentinel LN biopsy [27] do not always improve survival in patients with cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The development of new methods to detect and treat metastasis in false-N0 LNs will be extremely important. In previous studies, we have shown that a lymphatic drug delivery system has great potential in the therapeutic and prophylactic treatment of false-N0 LNs [25,26] , and we expect this technique to be applied in the clinical setting in future.…”
Section: Discussionmentioning
confidence: 99%